1962
DOI: 10.1007/bf01451369
|View full text |Cite
|
Sign up to set email alerts
|

�ber die Werte der Dedekindschen Zetafunktion

Abstract: Verzichtet man auf eine arithmetische Deutung yon r, so w/~re es wiinsehenswert, einen einfaeheren Zugang zu obiger Formel zu haben. I n dieser Arbeit soll ein etementarer funktionentheoretiseher Beweis durchgeffihrt werden, zu dem reich Herr Professor SIEGEL anregte und welcher nur leieht beweisbare S/~tze fiber die Hilbertsehen Modulfunktionen und elementare Eliminationstheorie benutzt.Das Ergebnis ist etwas welter als (1), es wird n/~mlieh die entsprechende Aussage bewiesen ffir die Dedekindsehen Zetafunkti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
6

Year Published

1962
1962
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 10 publications
1
36
0
6
Order By: Relevance
“…Since it is only (K(2) which can be interpreted geometrically in this way, we did not get a formula for (r(2m), m>l. However, we conjecture that an analogous result holds here, namely: (3) agrees with the function A(x) in Theorem 1.…”
Section: ~R(2)=~-x ~ Cva(x~l)a(xvs) (Finite Sum)mentioning
confidence: 49%
See 1 more Smart Citation
“…Since it is only (K(2) which can be interpreted geometrically in this way, we did not get a formula for (r(2m), m>l. However, we conjecture that an analogous result holds here, namely: (3) agrees with the function A(x) in Theorem 1.…”
Section: ~R(2)=~-x ~ Cva(x~l)a(xvs) (Finite Sum)mentioning
confidence: 49%
“…A famous theorem, proved by Euler in 1734, is that the sum rational multiple of ~2m for all natural numbers m: This result was generalized some years ago by Klingen [3] and Siegel [5], who showed that for an arbitrary totally real number field K the value of the Dedekind zeta function 1 …”
mentioning
confidence: 97%
“…Via C.L. Siegel and H. Klingen [4,8], if χ denotes a Dirichlet character and K is a totally real number field, then the Dirichlet L-function L(χ, s) lies in Q(χ) when s takes negative integer values. For a representation ρ, the associated character will simply be written as χ ρ .…”
Section: Introductionmentioning
confidence: 99%
“…Note that the summation in (1.8) is taken over totally positive elements of a −1 . Special values of ζ(a, f∞, s) at negative integers turns out to be rational numbers (see [Kli62], [Sie69] and [Shi76]). These rational numbers satisfy many remarkable congruence relations which have been exploited by many number theorists to construct various p-adic objects.…”
mentioning
confidence: 99%